Pembelarajan Daring Pendidikan Seni Rupa Mahasiswa PGSD Universitas Muhammadiyah Sukabumi di Masa Pandemi Covid-19 - Irmawati, Irmawati; Khaleda , Irna; Sutisnawati, Astri (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2023)
Abstract: This research is entitled Online Learning of Fine Arts Education for PGSD Students of Muhammadiyah Sukabumi University during the Covid-19 Pandemic, which aims to describe the learning process of fine arts education for PGSD students at Muhammadiyah University of Sukabumi during the Covid-19 pandemic, and the obstacles faced by PGSD students of Muhammadiyah University of Sukabumi during the learning process during the Covid-19 pandemic. To explore the data, a descriptive analysis method was used with a qualitative approach. The reason for using this method is that it is in accordance with the research objectives which want to describe and describe the process of learning fine arts education during the Covid-19 pandemic and the obstacles faced. The findings of the research show that: the learning process of fine arts education for PGSD Muhammadiyah University students in Sukabumi during the Covid-19 pandemic requires using several applications to achieve learning, As for the applications used, namely the Whatsapp group, and Instagram and the material presented in this online lecture, one of which is the Three-Dimensional Artwork by making works of art in the form of a corona virus, it is hoped that these works of art can become monumental works that can be remembered from one generation to another the next generation, that all people in the world have experienced difficult times during the Covid-19 pandemic. The process of making this work took approximately 4 weeks from 30 May 2020 - 4 June 2020. Then the obstacles faced by PGSD students of Muhammadiyah Sukabumi University during the learning process during the Covid-19 pandemic were very diverse, including internet signal and quota, stable internet signal and availability of quotas are very important because if one or both of them are inadequate, it will certainly interfere with the lecture process.